The Bibliographical Maker Movement - Jacobs, Courtney “Jet”; McIntosh, Marcia; O’Sullivan, Kevin M. (Knygotyra, 2022)
At the end of the twentieth century, increased access to certain technologies and processes, such as 3D scanning, computer-aided design, rapid fabrication and microcircuitry, enabled consumers to become creators of material design. These activities, which collectively came to be known as making, extended across both public and private sectors, including the study of the book. This paper offers an extended discourse on the full range of activities comprising the bibliographical maker movement, which in recent years has coalesced around the idea that maker culture may be employed to enhance our understanding of not only the history but also the future of the book. The application of these new technologies toward critical book studies has proceeded from the practice-based approach to research and instruction first begun under the auspices of the bibliographical press movement in the mid-twentieth century. In keeping with this earlier work, biblio-making is predicated upon the idea that certain kinds of knowledge are best gained through personal experience and experimentation. This article will first outline the benefits of applying 3D technologies to the goals of book history before locating and describing the activities of participating individuals and institutions within three broad categories: holistic, 3D digitisation; recovering historical tools and processes; and creative experiments in book design. As the article demonstrates, the strength and potential of the bibliographical maker movement lies in its widening community of practice and that, by virtue of its being an open-access network of constituents, it is now poised to make a significant and lasting contribution to the study of the book.
Keywords: Bibliography; maker culture; book history; 3D technologies; bibliographical press movement; bibliographical maker movement; artists’ books